2019
DOI: 10.1126/sciadv.aax1697
|View full text |Cite
|
Sign up to set email alerts
|

Past East Asian monsoon evolution controlled by paleogeography, not CO 2

Abstract: The East Asian monsoon plays an integral role in human society, yet its geological history and controlling processes are poorly understood. Using a general circulation model and geological data, we explore the drivers controlling the evolution of the monsoon system over the past 150 million years. In contrast to previous work, we find that the monsoon is controlled primarily by changes in paleogeography, with little influence from atmospheric CO 2 . We associate increased precipitation since the Late Cretaceou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
219
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 249 publications
(231 citation statements)
references
References 127 publications
11
219
1
Order By: Relevance
“…However, a higher plateau will increase the flux of moisture towards it due to greater thermal forcing as a deeper low-pressure system develops. Also, Farnsworth et al (2019) showed that a plateau of half the height of today's Tibetan Plateau can limit convective processes, capping them in the lower troposphere and so inhibiting precipitation as seen today on the Iranian Plateau.
Fig.
…”
Section: The Topographic Evolution Of the Tibetan Regionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a higher plateau will increase the flux of moisture towards it due to greater thermal forcing as a deeper low-pressure system develops. Also, Farnsworth et al (2019) showed that a plateau of half the height of today's Tibetan Plateau can limit convective processes, capping them in the lower troposphere and so inhibiting precipitation as seen today on the Iranian Plateau.
Fig.
…”
Section: The Topographic Evolution Of the Tibetan Regionmentioning
confidence: 99%
“…Proxy data and modelling show that, although still present in the early Cretaceous, a monsoon climate all but disappeared over southern China during the late Cretaceous and early Paleocene (see Farnsworth et al., 2019 , and references therein) ( Fig. 1 b).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations